(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
A skill assessment is a process that evaluates an individual’s knowledge, abilities, and competencies in a specific area or field. It involves comparing a person’s actual performance with a specified standard and evaluating whether it meets or exceeds the requirements. Alternative Assessment is a method of evaluation that measures a student’s level of proficiency in a subject as opposed to the student’s level of knowledge. The overall goal of alternative assessment is to allow students to demonstrate their knowledge and execute tasks. Alternative assessment is also called a performance test or authentic assessment because it is deeply rooted in one’s ability to do something by leveraging newly-gained knowledge. As part of the assessment, the student will need to perform meaningful tasks that reflect a clear understanding of the teaching and learning objectives. Competence assessment is a process in which evidence is gathered by the assessor and evaluated against agreed criteria in order to make a judgement of competence. Skill assessment is the comparison of actual performance of a skill with the specified standard for performance of that skill under the circumstances specified by the standard and evaluating whether the performance meets or exceed the requirements. Assessment of a skill should comply with the four principles of validity, reliability, fairness and flexibility. Formative assessment provides feedback for remedial work and coaching, while summative assessment checks whether the competence has been achieved at the end of training. Assessment of combinations of skills and their foundational knowledge may provide greater efficiency, and in some cases competence in one skill my imply competence in other skills. The thoroughness rewired of assessment may depend on the consequences of occasional poor performance.